Global Information Technologies 2008
DOI: 10.4018/978-1-59904-939-7.ch036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Modularity in Free/Open Source Software Development

Abstract: Software design and development in Free/Open Source projects are analyzed through the lens of the theory of modularity applied to complex systems. We show that both the architecture of the artifacts (software) and the organization of the projects benefited from the paradigm of modularity in an original and effective manner. In particular, our analysis on empirical evidence suggests that three main shortcuts to modular design have been introduced and effectively applied. First, some successful projects inherite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…David and Ghosh (2008) have shown that the structure of the technical interdependencies between the different modules composing Linux have a certain degree of correspondence to the pattern of social ties the authors of those modules have built through past collaboration. A similar perspective emerges from the analysis undertaken by Narduzzo and Rossi (2005) in their effort to define modularity in the OSS context. In OSS the architecture of the software is likely to be constantly changed over time, and so is the degree of modularization it embodies.…”
Section: Modular Structure Of Codementioning
confidence: 78%
See 3 more Smart Citations
“…David and Ghosh (2008) have shown that the structure of the technical interdependencies between the different modules composing Linux have a certain degree of correspondence to the pattern of social ties the authors of those modules have built through past collaboration. A similar perspective emerges from the analysis undertaken by Narduzzo and Rossi (2005) in their effort to define modularity in the OSS context. In OSS the architecture of the software is likely to be constantly changed over time, and so is the degree of modularization it embodies.…”
Section: Modular Structure Of Codementioning
confidence: 78%
“…In self-organized social bodies it is however difficult for architects to master the process in the same way they could do in a firm. The main problem is that it is very difficult to develop a fullfledged architecture at the beginning of a self-organized process of development: self-organization by nature implies a bottom up approach to coordination (von Krogh et al, 2012;David & Rullani, 2008;Lanzara & Morner, 2005), involving the risk that developers split into different and potentially incompatible software (Dalle & Juillen, 2003;Narduzzo & Rossi, 2005). The potential of providing coordination by leadership is limited by the same factors.…”
Section: Modular Structure Of Codementioning
confidence: 99%
See 2 more Smart Citations
“…We call them community‐led projects. The high–high case usually comes up when a software project has a stable design and when it is structurally possible to break it in many independent modules that are suitable for large‐scale team development (Narduzzo & Rossi, 2005). In many cases, the design originates from an established standard.…”
Section: A Model For Open Source Softwarementioning
confidence: 99%